Expression of GARP Is Increased in Tumor-Infiltrating Regulatory T Cells and Is Correlated to Clinicopathology of Lung Cancer Patients - Jin, Hao; Sun, Liping; Tang, Lu; Yu, Wenwen; Li, Hui (Frontiers in Immunology, 2017)
Regulatory T cells (Tregs) are immunosuppressive T cells that play an important role in immune homeostasis. Multiple markers have been associated with the characterization, as well as function of Tregs. Recently, glycoprotein A repetitions predominant (GARP), a transmembrane protein containing leucine rich repeats, has been found to be highly expressed on the surface of activated Tregs. GARP maintains Tregs’ regulatory function and homeostasis through the activation and secretion of transforming growth factor  (TGF-). In this study we investigated the expression of GARP in Tregs from the peripheral blood (PB) and tumor tissues of lung cancer patients. The association between the proportion and expression level of GARP on Tregs and the clinicopathological factors of lung cancer patients was also analyzed. Results showed that in the tumor tissues of patients with lung cancer, GARP expression was increased in Tregs and was associated with lymph node metastasis, distant metastasis and clinical stage. Furthermore, the infiltrating Tregs from early stage patients exhibited higher GARP expression than that from advanced cancer patients, which indicated that GARP might be an early prognostic biomarker. In vitro co-culture studies demonstrated that human lung cancer cell lines might induce the expression of GARP in Tregs by certain mechanisms. Overall, this research demonstrated the potential value of GARP in Tregs definition and cancer immunotherapy.